Causes, consequences, and strategies to deal with information overload: A scoping review - Leila Shahrzadi; Ali Mansouri; Mousa Alavi; Ahmad Shabani (International Journal of Information Management Data Insights)
The exponential growth of digital information has led to the pervasive problem of information overload, affecting decision-making, productivity, and well-being. This article reviews the existing literature on the various effects of information overload, its underlying causes, and strategies for managing it. A scoping review of English literature up until January 2023 was conducted using Scopus, Web of Science, PubMed, and Emerald. The findings reveal that information overload is caused by personal factors, information characteristics, task parameters, organizational parameters, and information technology parameters. The effects include poor decision-making, decreased productivity, and cognitive pressures. Strategies for managing information overload include learning multiple skills and using filtering, prioritizing, and technology tools. This article provides a foundation for future research and interventions in this area.